(untitled) (Biocenosis, 2021)
The purpose of this investigation is to determine the status of the environmental commitment situation of the Higher and Technical Educational Institutions (IEST by its acronym in Spanish) of Costa Rica using a survey already applied in other countries, which originates from another more extensive, already carried out, study. This instrument seeks to understand the scope of real work by the institutions through the application of a survey of 25 closed questions and two more complementary open questions, with each of the questions adding one point in the evaluation, where the greater the number of points, the better the score. Certainly, the general sample results obtained place the country at an intermediate level of institutionalization of environmental commitment with opportunities for improvement in the fields of teaching (2.6), research (1.8), the government (3,4), and management (3,4). In addition, IEST members of the Costa Rican Network of Sustainable Educational Institutions (REDIES) were revealed to outperform those that are not part of this Network according to the results obtained.